Dynastic Decline in Eastern Han. Issue 1 (2nd January 2019) - Loewe, Michael
Abstract : Dynastic cohesion of the Eastern Han declined from ca. 130 CE or earlier as may be seen in the absence of a decisive emperor, the treatment of his blood relatives, the growth of privately managed estates, and the cessation of measures to relieve distress and settle the population. To this we may add the growth of some types of groups of non-official influential individuals bearing various titles, and the expressions of a sharp criticism of the conduct of public life that accompanied the central government's loss of strength.